HER2-targeted therapies in cancer: a systematic review - Kunrui Zhu; Xinyi Yang; Hebei Tai; Xiaorong Zhong; Ting Luo; Hong Zheng (BMC, 2024)
Abstract Abnormal alterations in human epidermal growth factor receptor 2 (HER2, neu, and erbB2) are associated with the development of many tumors. It is currently a crucial treatment for multiple cancers. Advanced in molecular biology and further exploration of the HER2-mediated pathway have promoted the development of medicine design and combination drug regimens. An increasing number of HER2-targeted drugs including specific monoclonal antibodies, tyrosine kinase inhibitors (TKIs), and antibody-drug conjugates (ADCs) have been approved by the U.S. Food and Drug Administration. The emergence of ADCs, has significantly transformed the treatment landscape for various tumors, such as breast, gastric, and bladder cancer. Classic monoclonal antibodies and novel TKIs have not only demonstrated remarkable efficacy, but also expanded their indications, with ADCs in particular exhibiting profound clinical applications. Moreover the concept of low HER2 expression signifies a breakthrough in HER2-targeted therapy, indicating that an increasing number of tumors and patients will benefit from this approach. This article, provides a comprehensive review of the underlying mechanism of action, representative drugs, corresponding clinical trials, recent advancements, and future research directions pertaining to HER2-targeted therapy.